[Ultrastructure changes of sciatic peripheral nerve of rat’s onconditions of pharmacological correction] - Demidchuk A.S. (Морфологія, 2015)
Background. Different modifications of surgical interventions and conservative treatment do not lead to the full restoration of lost limb functions in the early stages of rehabilitation. The postoperative complications include patients with delayed nerve regeneration which requires re-operation for nerve trunks and application of new methods of rehabilitation. Pharmacological treatment with neuropeptides has a trophic, anti-inflammatory effect, improves blood and lymph circulation, has a positive effect on the central nervous system. Objective. The purpose of the study was to compare ultrastructural changes of peripheral nerve of rats under conditions of neuropeptides treatment and without pharmacotherapy after 6 and 12 weeks after injury. Methods and results. The research was conducted on white rats which were divided into three groups. The experimental model of sciatic nerve injury was reproduced in all groups of animals. In postoperative period rats of the first group did not receive pharmacological correction. The rats of the second group received сerebrolysinum in the dose of 0,02 mg/kg daily during 21 day postoperatively. The third group of animals received сerebralum in the dose of 0,02 mg/kg daily during three days postoperatively. We investigated the ultrastructural characteristics of the sub-segment of the sciatic nerve after 6 and 12 weeks after injury in three groups of animals using electron microscopic techniques. Conclusion. The process of sciatic nerve regeneration was the most effective in the group of animals with the pharmacological correction by Cerebralum. Citation: Demidchuk AS. [Ultrastructure changes of sciatic peripheral nerve of rat’s onconditions of pharmacological correction]. Morphologia. 2015;9(3):18-21. Ukrainian.